PENGARUH KEBIJAKAN PAJAK, AKSES KEUANGAN DAN NIAT TERHADAP PERILAKU BERWIRAUSAHA MAHASISWA GENERASI Z DI KOTA BATAM - LIDIA ANGEL (LPPM Universitas Putera Batam, 2025)
This study was conducted to examine the influence of factors influencing the Entrepreneurial Behavior of Generation Z Students in Batam City. These factors include Tax Policy, Financial Access, and Intention. This study used a quantitative approach where the data were obtained primarily by distributing questionnaires. The population in this study amounted to 36,065 students. The sample taken was 100 people using the Slovin formula with a 10% error rate. The testing techniques in this study consisted of descriptive analysis, instrument testing, classical assumption testing, multiple linear regression testing, and hypothesis testing with data processing using SPSS version 29. The results of this study state that Tax Policy, Financial Access, and Intention simultaneously have a significant effect on Entrepreneurial Behavior. The conclusion based on the results of the study is that H1 is accepted, H2 is accepted, H3 is accepted, H4 is accepted.